Doping type influence on physical diamond properties. (4th February 2022) - Itsh'ak, Azoulay; Klonsky, Ory; Gelbstein, Yaniv; Beker, Peter
Abstract: Diamond exhibits outstanding properties that make it a material of interest for the semiconductors industry. The industry required a silicon alternative that enabled devices to be smaller, cooler, faster, more powerful and cleaner. Diamond exhibit a large energy band gap that needs to be doped in order to observe any significant electrical conductivity. The purpose of this work is to compare the electrical properties of intrinsic and doped diamond based materials by impedance spectroscopy, I-V measurements and thermal conductivity measurements. The results of impedance measurement of the real and imaginary parts were presented in the form of a Nyquist and dielectric permittivity curves. In order to interpret the observed response, a resistor–capacitor circuit model was used for physical mechanisms interpretation. Direct evidence for the doping influence on the diamond, was obtained by I-V measurements. We describe Raman spectroscopy based method of measuring thermal conductivity of diamond doped samples, and review results achieved by line width correlation technique.